ROMANSY 18 Robot Design, Dynamics and Control Proceedings of The Eighteenth CISM-IFToMM Symposium - Parenti Castelli, Vincenzo; Schiehlen, Werner; SpringerLink (Online service) (Vienna : Springer Vienna, 2010)
The papers in this volume provide a vision of the evolution of the robotics disciplines and indicate new directions in which these disciplines are foreseen to develop. Paper topics include, but are not limited to, novel robot design and robot modules/components, service, education, medical, space, welfare and rescue robots, humanoid robots, bio-robotics, multi-robot, embodied multi-agent systems, challenges in control, modeling, kinematical and dynamical analysis of robotic systems, innovations in sensor systems for robots and perception, and recent advances in robotics. In particular, many contributions on humanoid robots from leading Japanese researchers are included.
Keynote Lectures -- Where Future Robots should Go and should not Go -- Robust Drives for Parallel Robots -- Minimal-Form Multibody Dynamics for Embedded Multidisciplinary Applications -- Novel Robot Design and Robot Modules/Components -- Constructive Redesign of a Modular Metamorphic Microgripper -- A One-Motor Full-Mobility 6-PUS Manipulator -- Dynamic Hybrid Position/Force Control for Parallel Robot Manipulators -- Decoupled Parallel Manipulator with Universal Joints and Additional Constraints -- Positio: A 4R Serial Manipulator Having a Surface of Isotropic Positioning -- Joint space and workspace analysis of a two-DOF closed-chain manipulator -- Identification of Base Parameters for Large-scale Kinematic Chains Based on Physical Consistency Approximation by Polyhedral Convex Cones -- Modeling Effects on Free Vibration of a Two-Link Flexible Manipulator -- Chatter Suppression in Sliding Mode Control: Strategies and Tuning Methods -- On Solving the Forward Kinematics of the 6-6 General Parallel Manipulator with an Efficient Evolutionary Algorithm -- Determination of Mobility in a Kinematic Chain by Properly Using the Jacobian Matrix -- Micro Hinges and their Application to Micro Robot Mechanisms -- Parallel RPR-?-RPR Manipulator Generating 2-DOF Translation along One-Sheet Revolute Hyperboloid -- A Study on the Effects of Cable Mass and Elasticity in Cable-Based Parallel Manipulators -- Service, Education, Medical, Space, Welfare and Rescue Robots -- Motion Planning of the Trident Snake Robot: An Endogenous Configuration Space Approach -- A Novel Stair-Climbing Wheelchair with Variable Configuration Four-Bar Linkage $1 (BMechanism Design and Kinematics$1 (B-- Motion and Force measures on tortoises to design and control a biomimetic quadruped robot -- Mechanism Design Improvements of the Airway Management Training System WKA-3 -- Design for a Dual-Arm Space Robot -- Mechanical Design of a Novel Biped Climbing and Walking Robot -- Humanoid Robots, Bio-Robotics, Multi-Robot, Multi-Agent Systems -- Development of the Anthropomorphic Waseda Saxophonist Robot -- Design and Simulation of a Waist-Trunk System for a Humanoid Robot -- Safe Navigation in Dynamic Environments -- Development of a Visual Interface for Sound Parameter Calibration of the Waseda Flutist Robot WF-4RIV -- Simulation of a Humanoid Robot walking gait on Moon Surface -- Development of New Biped Foot Mechanism Mimicking Human$1 (Bs Foot Arch Structure -- Design and Development of Bio-mimetic Quadruped Robot -- Static and Dynamic Maneuvers With a Tendon-Coupled Biped Robot -- Control, Modelling, and Analysis of Robotic Systems -- Kinematic Calibration of Small Robotic Work Spaces Using Fringe Projection -- Forward Dynamics of 3-DOF Parallel Robots: a Comparison Among Different Models -- Workspace Generation of Planar Wire-Actuated Parallel Manipulators with Antipodal Method -- Trajectory Following and Vibration Control for Flexible-link Manipulators -- Shaking Forces Minimization of High-Speed Robots via an Optimal Motion Planning -- Passivity Based Backstepping Control of an Elastic Robot -- Economical Control of Robot Systems Using Potential Energy -- Motion Control of an Under-Actuated Service Robot Using Natural Coordinates -- Control Law Synthesis for Slip Reduction of Wheeled Robot -- A Kinematic Model of the Tibio-Talar Joint Using a Minimum Energy Principle -- Innovations in Sensor Systems for Robots and Perception -- Development of the Ultrasound Probe Holding Robot WTA-1RII and an Automated Scanning Algorithm based on Ultrasound Image Feedback -- RFID-Assisted Detection and Handling of Packages -- Virtual Haptic Map Using Haptic Display Technology for Visually Impaired -- Extraction of Semantic Information from the 3D Laser Range Finder -- The Application of ICP and SIFT Algorithms for Mobile Robot Localization -- Estimation of Complex Anatomical Joint Motions Using a Spatial Goniometer -- Recent Advances in Robotics -- Modeling and Motion Planning for a Population of Mobile Robots -- Reconfigurable Planar Three-Legged Parallel Manipulators -- Multi-Objective Trajectory Planning in Wire-Actuated Parallel Manipulators -- Design of the Facial Expression Mechanism for Humanoid Robots -- A Method for Comparing Human Postures from Motion Capture Data -- Evaluation of the KOBIAN and HABIAN Emotion Expression Humanoid Robots with European Elderly People -- An Approach to the Dynamics and Kinematical Control of Motion Systems Consisting of a Chain of Bodies -- Modular Design of Emotion Expression Humanoid Robot KOBIAN -- A Random-Profile Approach for Trajectory Planning of Wheeled Mobile Robots With non-Slipping Constraint -- The Second Type of Singularity Analysis of the New Parallel Manipulator with 6 Degree-of-Freedom.s
Keywords: Engineering; Vibration; Engineering; Robotics and Automation; Vibration, Dynamical Systems, Control